ForeSight-AI-based Smart Living Platform Approach - Bauer, Jochen; Hechtel, Michael; Konrad, Christoph; Holzwarth, Martin; Mayr, Andreas; Schneider, Sven; Franke, Jörg; Hoffmann, Hilko; Zinnikus, Ingo; Feld, Thomas; Runge, Mathias; Hinz, Oliver (Current Directions in Biomedical Engineering, 2020)
In the upcoming years, the internet of things (IoT) will enrich daily life. The combination of artificial intelligence (AI) and highly interoperable systems will bring contextsensitive multi-domain services to reality. This paper describes a concept for an AI-based smart living platform with open-HAB, a smart home middleware, andWeb of Things (WoT) as key components of our approach. The platform concept considers different stakeholders, i.e. the housing industry, service providers, and tenants. These activities are part of the Fore-Sight project, an AI-driven, context-sensitive smart living platform.
CRIS-Team Scopus Importer:2021-04-19
Keywords: interoperability; smart home; smart living; web of things

ForeSight - An AI-driven Smart Living Platform, Approach to Add Access Control to openHAB - Bauer, Jochen; Hechtel, Michael; Konrad, Christoph; Holzwarth, Martin; Hoffmann, Hilko; Feld, Thomas; Schneider, Sven; Zinnikus, Ingo; Mayr, Andreas; Franke, Jörg (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2020)
We created an approach for a smart living platform called ForeSight which consists of different modules: a service engineering module, a Web of Things (WoT)-based Internet of Things (IoT) module and an artificial intelligence (AI) component. This paper describes how openHAB, a smart home middleware, is extended to fulfill platform requirements related to a successful interaction with the IoT module of ForeSight, more precisely, to add identity and access management (IAM) to openHAB and comply with European privacy laws.
Created from Fastlane, Scopus look-up
Keywords: Architecture; Artificial intelligence; openHAB; Platform; Privacy; Smart home; Smart living